Low velocity impact performance of fiber-reinforced polymer impregnated with shear thickening fluid - Li Sun; Minghai Wei; Jie Zhu (Polymer Testing, 2021)
In this study, the mechanical performance of fiber-reinforced polymer (FRP) impregnated with shear thickening fluid (STF) under low-velocity impact was investigated. Three types of FRPs, with basalt (BFRP), carbon (CFRP), and glass (GFRP) fibers were prepared and 20 wt% STF was impregnated into these FRPs to develop FRP composite materials. The resistive force and energy dissipation of STF-impregnated FRP (FRP-STF) specimens and corresponding neat FRP specimens were evaluated using a drop hammer test. The test results demonstrate that the impregnation of the STF can effectively enhance the impact resistance performance of the three FRPs. Nevertheless, the enhancing effect and mechanism are different for different FRP types. For the BFRP and CFRP, the STF only improves their mechanical performance, while for the GFRP, the STF changes its mechanical mechanism. In terms of maximum enhancement resistive force, the STF has a significant effect on the CFRP, with a 78.0% increase compared to neat CFRP. In addition, the GFRP-STF shows excellent energy dissipation performance; the energy absorbability is increased to 90.7%, an increase of 119% compared to neat GFRP.